Dependence of Ca2+-Induced Contraction on ATP in α-Toxin-Permeabilized Preparations of Rat Femoral Artery - Masahiko Kushida; Tadayoshi Takeuchi; Akikazu Fujita; Fumiaki Hata (Elsevier, 2003)
ABSTRACT: Effects of various concentrations of ATP on Ca2+-induced contraction were studied in a-toxin-permeabilized preparations obtained from the rat femoral artery. The contractile magnitude was highest in the presence of 1 mM ATP and decreased with both increasing and decreasing the concentration, suggesting the presence of an optimum ATP concentration in inducing contraction. The magnitude of the contractions in various concentrations of ATP correlated with the extent of the phosphorylated myosin light chain (MLC). The rate of contractions in the presence of 1 mM ATP under an inhibition of MLC phosphatase was faster than in the presence of 4 mM ATP, suggesting that the increased phosphorylation of MLC at 1 mM ATP results from an increased activity of MLC kinase. On the other hand, MLC phosphatase activity appeared unchanged, because the rates of relaxations under the inhibition of MLC kinase were not different in the presence of either 1 or 4 mM ATP. The high sensitivity to 1 mM ATP was absent in the preparations that were permeabilized with β-escin or Triton X-100, suggesting the existence of an intracellular factor required for the increased activity of MLC kinase to ATP in the α-toxin-permeabilized preparations of the rat femoral artery.